Sustainable Catalytic Process for Synthesis of Triethyl Citrate Plasticizer over Phosphonated USY Zeolite - Kakasaheb Y. Nandiwaleand; Vijay V. Bokade (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Fruits wastage is harmful to health and environment concerning spreading diseases and soil pollution, respectively. To avoid this issue, use of citrus fruit waste for the production of citric acid (CA) is one of viable mean to obtain value added chemicals. Moreover, synthesis of triethyl citrate (TEC), a non-toxic plasticizer by esterification of CA with ethanol over heterogeneous catalyst would be renewable and sustainable catalytic process. In this context, parent Ultrastable Y (USY) and different percentage phosphonated USY (P-USY) zeolites were used for the synthesis of TEC in a closed batch reactor, for the first time. The synthesized catalysts were characterized by N2-adsorption desorption isotherm, powder X-ray diffraction (XRD) and NH3 temperature programmed desorption (TPD. Effect of reaction conditions, such as the molar ratio of ethanol to CA (5:1 - 20:1), the catalyst to CA ratio (0.05 - 0.25) and reaction temperature (363-403 K), were studied in view to maximizing CA conversion and TEC yield. Phosphonated USY catalysts were found to be superior in activity (CA conversion and TEC yield) than parent USY, which is attributed to the increased in total acidity with phosphonation. Among the studied catalysts, the P2USY (2% phosphorous loaded on USY) was found to be an optimum catalyst with 99% CA conversion and 82% TEC yield, which is higher than the reported values. This study opens new avenues of research demonstrating principles of green chemistry such as easy separable and reusable catalyst, non-toxic product, bio-renewable synthetic route, milder operating parameters and waste minimization.